DINAMIKA MUSLIM AMERIKA:: Menepis Tudingan, Meluruskan Kesalahpahaman - Bahrul Ulum (LP3M IAI Al-Qolam Malang, 2019)
After the September 11th Tragedy, it was a kind of guarantee of an interesting discussion to be observed especially for observers of the Muslim world and the West. the incident certainly happened pros and cons both in the Muslim world, especially for the Western world. The event became a kind of anomaly of attitude. On one hand, the humanitarian tragedy tore apart the relational harmony between religions in America, but on the other hand, more people were interested in studying Islam and the Islamic world, it even became a magnet for other religious communities to convert to Islam. The following article is certainly not enough to meet the expectations in viewing clearly the sad events. The approach in this paper uses historical flow. This paper shows that although Protestantism is the dominant group in America, the role of Judaism and Islam cannot be underestimated, because although the initial motive for the arrival of Muslim immigrants to America was economic problems and the improvement of fate, it must be admitted that there was a kind of anxiety from the West, that they will bring religious ideology and build communities according to the ideology of their ancestral lands. Meanwhile, the four groups of religious attitudes towards American students are: groups with deep commitment, rigid in responding to religion; groups with deep, flexible, and open commitment; critical groups; as well as cynical groups and ignore religious commitments.